Acute and sub-acute oral toxicity of Dracaena cinnabari resin methanol extract in rats - Al-Afifi, N.A.; Alabsi, A.M.; Bakri, M.M.; Ramanathan, A. (BioMed Central, 2018)
Background: Dracaena cinnabari (DC) is a perennial tree that located on the Southern coast of Yemen native to the Socotra Island. This tree produces a deep red resin known as the Dragon's blood, the Twobrother's Blood or Damm Alakhwain. The current study performed to evaluate the safety of the DC resin methanol extract after a single or 28 consecutive daily oral administrations. Methods: In assessing the safety of DC resin methanol extract, acute and sub-acute oral toxicity tests performed following OECD guidelines 423 and 407, respectively, with slight modifications. In acute oral toxicity test, DC resin methanol extract administered to female Sprague Dawley rats by oral gavage at a single dose of 300 and 2000 mg/kg body weight. Rats observed for toxic signs for 14 days. In sub-acute oral toxicity test, DC resin methanol extract administered to the rats by oral gavage at 500, 1000, and 1500 mg/kg body weight daily up to 28 days to male and female Spradgue Dawley rats. The control and high dose in satellite groups were also maintained and handled as the previous groups to determine the late onset toxicity of DC resin methanol extract. At the end of each test, hematological and biochemical analysis of the collected blood were performed as well as gross and microscopic pathology. Results: In acute oral toxicity, no treatment-related death or toxic signs were observed. It revealed that the DC resin methanol extract could be well tolerated up to the dose 2000 mg/kg body weight and could be classified as Category 5. The sub-acute test observations indicated that there are no treatment-related changes up to the high dose level compared to the control. Food consumption, body weight, organ weight, hematological parameters, biochemical parameters and histopathological examination (liver, kidney, heart, spleen and lung) revealed no abnormalities. Water intake was significantly higher in the DC resin methanol extract treated groups compared to the control. Conclusion: This study demonstrates tolerability of DC resin methanol extract administered daily for 28 days up to 1500 mg/kg dose.